1996
DOI: 10.1002/jor.1100140112
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin‐6 in osteoarthritic chondrocytes and effects of fluid‐induced shear on this expression in normal human chondrocytes in vitro

Abstract: This study tested the effect of fluid-induced shear on interleukin-6 expression in normal human articular chondrocytes in vitro. As determined by Northern blot analysis, interleukin-6 mRNA expression occurs in chondrocytes from osteoarthritic cartilage but not in normal chondrocytes. Applying fluid-induced shear stress to primary high density cultures of chondrocytes increased interleukin-6 mRNA signal 4-fold at 1 hour and 10 to 15-fold at 48 hours compared with unsheared control cultures. At 48 hours, fluid-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 56 publications
3
74
0
Order By: Relevance
“…The confluent cells on glass slides were either kept as static controls or subjected to shear stress for 1.5 or 24 hours followed by RNA isolation and analysis. Previous studies (16,52,68) have demonstrated that chondrocyte responses were elicited by shear stress at such durations and a 1.6-Pa amplitude, which was used in the current study. The MMP-9 gene was induced in cells sheared for 1.5 and 24 hours (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The confluent cells on glass slides were either kept as static controls or subjected to shear stress for 1.5 or 24 hours followed by RNA isolation and analysis. Previous studies (16,52,68) have demonstrated that chondrocyte responses were elicited by shear stress at such durations and a 1.6-Pa amplitude, which was used in the current study. The MMP-9 gene was induced in cells sheared for 1.5 and 24 hours (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cytokine genes have a potential role in controlling the catabolic/anabolic balance of articular cartilage. Several cytokines are involved in cartilage metabolism and are synthesized by synovial cells and cartilage chondrocytes, among them IL-6 (Mohtai et al, 1996). IL-6 is believed to be one of the crucial factors in joint destruction, being a pleiotropic pro-inflammatory cytokine that is markedly upregulated at times of tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of IL-6 in response to different types of mechanical stresses has been reported in several cell types, such as vascular endothelial cells [41][42][43], vascular smooth muscle cells [44], cardiac myocytes [45], lung fibroblasts [46], and chondrocytes [47]. To investigate whether mechanical stress associated with mild fluctuations in IOP similar to those that may occur in normal physiologic conditions [7] could induce the production of IL-6 in TM cells, we selected a cyclic stretch regimen of 5% elongation per second as an in vitro model.…”
Section: Discussionmentioning
confidence: 99%